PERANCANGAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) BERBASIS WEB DI SMK BANTEN JAYA - Waliadi Gunawan; Andi Usri Usman; Riwan Febriyanto (LPPM Unbaja, 2021)
The rapid development of science and technology. Information technology can help in producing information systems that are fast, accurate, relevant and timely. information is needed in various sectors that will support developments in all fields and can help solve problems to get the right results. Web-Based Information System for New Student Admissions is a system designed to carry out automatic selection starting from the registration process, the selection process until announcement of the result which is made online and real time based. The online PPDB system is able to satisfy expectations among the people regarding the implementation of new student admission system that are objective, transparent, accountable, quick and accurate. In this Community Service, the focus is on the process of implementation new student admissions (PPDB) which is carried out online. Based on the results of the analysis, it can be concluded that the online admission process of new students (PPDB) has only been running for a year. This research method uses the Waterfall method. certainly in the process of implementation PPDB online there are still some things that need to be considered. As well as the socialization that was carried out, because not all people understand the existing technology, need specific part in the verification process according to the field of certificate being verified.